Defining covert recording: A qualitative study exploring the experiences of clinicians when a patient records a hospital clinical encounter using a smartphone without consent. (November 2022) - Ryan, Laura; Weir, Kelly A; Maskell, Jessica; Bevan, Lily; Le Brocque, Robyne
Background: Patients use their smartphones to covertly record their clinical encounters in hospital. However, this issue is poorly understood. Insight into the clinician perspective will help inform policies and practices that deliver safe environments for patients and clinicians. Objective: This study aimed to gain a deep understanding of clinician attitudes and behaviours when a patient covertly records a hospital clinical encounter using a smartphone. Methods: Semi-structured interviews were undertaken with 20 hospital clinicians. Participants were recruited via purposive and snowball sampling. Interviews were conducted in person or via Microsoft Teams. Interviews were digitally audio recorded and transcribed. Data was analysed using thematic analysis. Results: Most of the 20 participants reported they had either suspected or experienced a patient covertly recording a clinical encounter. Covert recordings occurred across a broad range of clinical disciplines and contexts. Themes were identified from participant perspectives, including discernment of patient intention, likeliness to consent to the recording if asked, anticipated risks and potential benefits associated with the covert recording. These themes have led to the categorisation of three forms of covert recording: (1) Intentional Covert Recording (2) Inadvertently – Covert Recording, and (3) Beneficial Covert Recording. Conclusion: Clinicians have varied experiences and responses when a patient covertly records a clinical encounter. Findings indicate that nuanced strategies may be required to support clinicians to manage covert recording, whilst balancing the needs of patients.